2002
DOI: 10.1002/ldr.517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Newbouldia laevis on soil subjected to shifting cultivation in the Ibadan area, southwestern Nigeria

Abstract: Newbouldia laevis is the most abundant tree in shifting cultivation farms in the Ibadan area of southwestern Nigeria, where shifting cultivation is undergoing intensification. The physical and chemical properties of the soil under and outside the canopies of N. laevis were compared in order to evaluate the effects of the tree on the soil. Thirty Newbouldia trees were studied in 10 plots that measured 25 Â 25 m. There was no significant increase in organic matter, total nitrogen, exchangeable calcium, magnesium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…16 Eighteen out of the twenty-five articles recount the conventional narrative that is the subject of this study. Of these eighteen, only four (Akobundu and Ekeleme, 2002;Aweto and Iyanda, 2003;Becker and Johnson, 2001;Duguma and Mollet, 1998) present any figures trying to compare past and current fallow lengths to support the claim of declines. Aweto and Iyanda (2003) give specific figures for fallows at present and in the past, but they do not cite any sources for such data or describe a survey that they undertook themselves.…”
Section: The Key Link In the Narrative: Declines In Fallow Lengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Eighteen out of the twenty-five articles recount the conventional narrative that is the subject of this study. Of these eighteen, only four (Akobundu and Ekeleme, 2002;Aweto and Iyanda, 2003;Becker and Johnson, 2001;Duguma and Mollet, 1998) present any figures trying to compare past and current fallow lengths to support the claim of declines. Aweto and Iyanda (2003) give specific figures for fallows at present and in the past, but they do not cite any sources for such data or describe a survey that they undertook themselves.…”
Section: The Key Link In the Narrative: Declines In Fallow Lengthsmentioning
confidence: 99%
“…Of these eighteen, only four (Akobundu and Ekeleme, 2002;Aweto and Iyanda, 2003;Becker and Johnson, 2001;Duguma and Mollet, 1998) present any figures trying to compare past and current fallow lengths to support the claim of declines. Aweto and Iyanda (2003) give specific figures for fallows at present and in the past, but they do not cite any sources for such data or describe a survey that they undertook themselves. In addition, the figures that they offer pertain to a particular region in southwestern Nigeria -Ikoyi -which is located 20 km away from Ibadan, a large city.…”
Section: The Key Link In the Narrative: Declines In Fallow Lengthsmentioning
confidence: 99%
“…Measurements were confined to the top 0-20 cm soils for the following reasons: (i) most significant changes in soil characteristics in any vegetation (especially in a tropical environment) are confined to the topmost layer of the soil profile (Aweto 1981;Aweto and Iyanda 2003); (ii) these depths cover the main distribution of roots and soil nutrient stocks of cocoa plantations (Hartemink 2005); (iii) biological processes, such as earthworm activities are restricted to 0-10 cm layer of tropical soils; (iv) to facilitate future replication of the methodology as routine soil samples are usually kept at top-soil layer (plough layer). Two categories of soil samples were taken at each sampling point to promote a detailed investigation of soil-property differences.…”
Section: Soil Sample Collection For Laboratory Analysismentioning
confidence: 99%
“…Sixty percent of studies on nutrient cycling found a positive effect of trees, 8% found a negative effect while 33% found no effect (Figure 4). Certain tree species increased nutrient cycling by retrieving sub-soil inorganic N and P from deep soils and cycling these to crops through decomposing biomass (Aweto & Iyanda 2003;Gindaba et al 2005). Biological nitrogen fixation represented the most effective type of nutrient cycling commonly used to accumulate nitrogen in the soil.…”
Section: Nutrient Cyclingmentioning
confidence: 99%